2014
DOI: 10.1155/2014/680962
|View full text |Cite
|
Sign up to set email alerts
|

Married Men Perceptions and Barriers to Participation in the Prevention of Mother-to-Child HIV Transmission Care in Osogbo, Nigeria

Abstract: Men's role in HIV prevention is pivotal to changing the course of the epidemic. Men's barriers toward participation in Prevention of Mother-to-Child Transmission (PMTCT) have not been adequately documented. This study is therefore designed to determine men's level of awareness and barriers to their participation in PMTCT programmes in Osogbo, Nigeria. This study was a descriptive qualitative one that utilized Focus Group Discussion (FGD). One-hundred and sixty married men were selected by convenience sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
4
11
0
Order By: Relevance
“…More than three quarter of the respondents were from the Yoruba ethnic group as revealed from the study, this is expected since the study is carried out in Ibadan North, a local government in the South-western part of Nigeria. The proportion of the respondents who practised Islam is higher compared to those who practiced Christianity and traditional religion which was similar to a research conducted in Osogbo (Adelekan et al, 2014) where more than three quarter of the respondents were Muslims. The educational status of men in the community can be considered to be less than average since less than half of them had at least secondary education.…”
Section: Discussionsupporting
confidence: 82%
“…More than three quarter of the respondents were from the Yoruba ethnic group as revealed from the study, this is expected since the study is carried out in Ibadan North, a local government in the South-western part of Nigeria. The proportion of the respondents who practised Islam is higher compared to those who practiced Christianity and traditional religion which was similar to a research conducted in Osogbo (Adelekan et al, 2014) where more than three quarter of the respondents were Muslims. The educational status of men in the community can be considered to be less than average since less than half of them had at least secondary education.…”
Section: Discussionsupporting
confidence: 82%
“…Despite the positive attitudes towards the roles of men expressed in this study, cultural factors are a hindrance to the execution of the roles. Culture relegates maternal and child caring aspects to women which remains consistent with findings by Adelekan (2014) who reported that men were unwilling to participate in PMTCT because it was culturally inappropriate [34]. Although assistance with household chores was highlighted in our study and in a previous study [5], the division of roles according to gender, prohibits men from assisting a pregnant or a nursing mother , because of the prevailing norm that household chores are for women [5].…”
Section: Roles Of Men In Pmtct Servicessupporting
confidence: 89%
“…Table 2 identifies basic characteristics of study setting and type of the included studies. Of the 44 articles included, 24 were qualitative studies [ 13 , 14 , 18 23 , 25 , 27 , 28 , 39 51 ], 10 were cross sectional studies [ 26 , 51 59 ], 3 were cohort studies [ 24 , 60 , 61 ], 3 were systematic reviews [ 12 , 16 , 17 ], 3 were randomised control trials [ 62 64 ], and 1 used mixed methods [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…“Few of the participants added a condition that their presence must be needed at the clinic before they could accompany their wife.” [ 18 ] pg 4…”
Section: Resultsmentioning
confidence: 99%